2021
DOI: 10.1155/2021/7386169
|View full text |Cite
|
Sign up to set email alerts
|

Shock Transfer in Futures and Spot Markets: An Agent-Based Simulation Modelling Method

Abstract: There have been heated debates about the role of stock index futures in the financial market, especially during the crash periods. In this paper, a multiagent spot-futures market model is developed to analyze the micromechanism of shock transfer across spot and futures markets. We assume that there are two stocks and one stock index futures contract in the spot-futures market. Agents are heterogeneous, including fundamentalists, chartists, noise traders, and arbitragers. The spot market and the futures market … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Kannika and James [38] focus on the single spot market and make probabilistic forecasts for natural gas in eight spot markets. Zhou and Li [39] underscore that arbitragers play an important role in spot-futures market interaction and shock transfer, and adequate arbitrage trading during crises may help eliminate the positive basis and halt the further spread of crises. Song and Xing [40] argued that after the implementation of the continuous trading system, Shanghai copper has a better price discovery function than London copper and New York copper futures.…”
Section: Cross-regional Arbitrage Between Futures and Spotmentioning
confidence: 99%
“…Kannika and James [38] focus on the single spot market and make probabilistic forecasts for natural gas in eight spot markets. Zhou and Li [39] underscore that arbitragers play an important role in spot-futures market interaction and shock transfer, and adequate arbitrage trading during crises may help eliminate the positive basis and halt the further spread of crises. Song and Xing [40] argued that after the implementation of the continuous trading system, Shanghai copper has a better price discovery function than London copper and New York copper futures.…”
Section: Cross-regional Arbitrage Between Futures and Spotmentioning
confidence: 99%
“…Similarly, Yang et al [ 23 ] used agent-based modeling to build a theoretical model of the order book and discovered that speculators, arbitrageurs, and hedgers play distinct roles in Chinese markets. Furthermore, Zhou & Li [ 24 ] constructed a multiagent spot-futures market model to examine the micromechanics of shock transfer and observed that arbitrageurs play a substantial role in spot-futures market contact and that appropriate arbitrage trading during crises can aid in reducing the positive basis and preventing the further spread of crises.…”
Section: Introductionmentioning
confidence: 99%